2018
DOI: 10.1002/14651858.cd011006.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for the treatment of depression in people with cancer

Abstract: Despite the impact of depression on people with cancer, the available studies were very few and of low quality. This review found very low certainty evidence for the effects of these drugs compared with placebo. On the basis of these results, clear implications for practice cannot be deduced. The use of antidepressants in people with cancer should be considered on an individual basis and, considering the lack of head-to-head data, the choice of which agent to prescribe may be based on the data on antidepressan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 149 publications
2
94
0
5
Order By: Relevance
“…The large discrepancy between rates of documented depressive symptoms and of use of antidepressant medications in our sample aligns with prior literature, which has demonstrated that most adults who screen positive for depression are not receiving treatment for depression, and conversely, most who receive depression treatment do not necessarily screen positive for depressive symptoms . Difficulties assessing depressive symptoms among patients with cancer could also contribute to this discrepancy, as oncology clinicians may struggle to distinguish between pathological mood symptoms and normal reactions to severe illness . Despite these challenges, our study suggests that active depressive symptoms documented by outpatient clinicians can help identify a high‐risk group of patients with advanced cancer.…”
Section: Discussionsupporting
confidence: 74%
“…The large discrepancy between rates of documented depressive symptoms and of use of antidepressant medications in our sample aligns with prior literature, which has demonstrated that most adults who screen positive for depression are not receiving treatment for depression, and conversely, most who receive depression treatment do not necessarily screen positive for depressive symptoms . Difficulties assessing depressive symptoms among patients with cancer could also contribute to this discrepancy, as oncology clinicians may struggle to distinguish between pathological mood symptoms and normal reactions to severe illness . Despite these challenges, our study suggests that active depressive symptoms documented by outpatient clinicians can help identify a high‐risk group of patients with advanced cancer.…”
Section: Discussionsupporting
confidence: 74%
“…There have been several meta-analyses of placebo controlled trials exploring the efficacy of anti-depressants in the treatment of cancer-related depression and they have generally failed to show a clear effect of anti-depressant treatment over placebo (Iovieno et al, 2011; Laoutidis and Mathiak, 2013; Ostuzzi et al, 2015). In a meta-analyses of anti-depressants for major depressive disorder in patients with comorbid medical disorders (including cancer), anti-depressants were more effective than placebo in some medical conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is an independent risk factor of early death in cancer patients (Arrieta et al, 2013; Pinquart and Duberstein, 2010). Antidepressants and, less frequently, benzodiazepines are used to treat depressed mood and anxiety in cancer patients, although evidence suggesting efficacy is limited and conflicting, and benzodiazepines are generally only recommended for short-term use because of side effects and withdrawal (Grassi et al, 2014; Ostuzzi et al, 2015; Walker et al, 2014). Although psychological approaches have shown only small to medium effects in treating emotional distress and quality of life, with low quality of reporting in many trials (Faller et al, 2013), there are several promising interventions utilizing existential orientations to psychotherapy (Breitbart et al, 2015; Spiegel, 2015).…”
Section: Introductionmentioning
confidence: 99%